IL-17-neutralizing antibody mitigates functional and structural changes in cigarette smoke-induced COPD model - Riani Moreira, Alyne; Uchoa da Silva, Camila; de Paula Costa Mattos, Leticia; Jesus Simão, Jussara; Camargo Berti, Veronica; Henrique Vasconcelos Alves, Luan; Ferreira da Silva, Alex; Jesus Lima, Franciele; Karoline Moreira Bezerra, Suellen; Nascimento Silva, Cintia; Cardoso Allonso- Vale, Maria Isabel; de Fatima Lopes Calvo Tiberio, Iolanda; et al. (Frontiers in Immunology, 2025)
Smoking remains the main risk factor for the development of chronic obstructive pulmonary disease (COPD). The inflammatory response mediated by innate and adaptive immune cells has been described in the development and progression of the disease, and the importance of Th17 cytokines has been observed. Studies have shown that blocking interleukin (IL)-17 can reduce inflammation in experimental models of lung injury. This study evaluated the effect of an IL-17 inhibitor in a cigarette smoke-induced COPD model in C57BL/6 mice. The effects of treatment with an IL-17 inhibitor were evaluated in an experimental model of COPD. Mice were exposed to cigarette smoke for 6 months, and treatment with IL-17 inhibitor was initiated in the fifth month. Four experimental groups were constituted: Control group—animals housed in a vivarium, receiving filtered room air; Control anti-IL-17 group—animals housed in a vivarium, receiving filtered room air and treatment with an anti-IL-17-neutralizing antibody; COPD group—animals exposed to cigarette smoke; and COPD anti-IL-17 group—animals exposed to cigarette smoke and treated with an anti-IL-17-neutralizing antibody. In the COPD groups, an increase in mean linear intercept was observed, along with a decrease in tissue elastance and tissue damping, confirming the COPD development. Administration of the IL-17-neutralizing antibody reversed these structural and functional alterations. Additionally, the COPD group exhibited an inflammatory response characterized by increased infiltration of polymorphonuclear and mononuclear cells and elevated numbers of IL-17- and IL-6-positive cells. These findings were consistent with the increased expression of IL-17 and IL-6 in lung homogenates, as assessed by ELISA. Treatment with the IL-17-neutralizing antibody effectively reversed this inflammatory response by reducing the expression of these inflammatory markers. These results were further supported by the evaluation of RORγt gene expression, which was significantly upregulated in the COPD group. Treatment with the IL-17-neutralizing antibody alleviates this upregulation. Thus, this study demonstrates, for the first time, the effectiveness of IL-17-neutralizing antibody treatment in a cigarette smoke-induced model of COPD, even after lung damage had been established, suggesting the therapeutic potential of IL-17-neutralizing antibodies in COPD.